NILAI FAKTOR KEMANAN PERKUATAN OPRIT JEMBATAN MENGGUNAKAN BAHAN GEOTEXTILE DAN CERUCUK GALAM pada TANAH LUNAK KOTA BANJARMASIN - Fitriansyah, Muhammad; Gustie Sambalewa Saky; Irwandy Muzaidi; Elia Anggarini (Universitas Muhammadiyah Surabaya, 2024)
Soft soils according to geotechnical guidelines relate to those soils that if not recognized and investigated carefully can cause intolerable long-term instability and settlement problems, such soils have low shear strength and high compressibility, The soft soil layer located in Banjarmasin, South Kalimantan has a thickness of up to 25 m, the average hard soil is found at a depth of about 40 m. The slope of the soil in Banjarmasin is between 0.13% with a geological composition, especially the bottom, dominated by clay with fine sand inserts and alluvium deposits consisting of gray-black and soft clay. The slope of the land in Banjarmasin is between 0.13% with a geological composition, especially the lower part dominated by clay with fine sand inserts and alluvium deposits consisting of grayish black clay and soft Research methods are a way to solve problems or how to develop knowledge with scientific methods. In this study, the analysis used is a comparison of the calculation of reinforcement on the bridge oprit manually with two methods of reinforcing galam cribs and Geotextile materials. The data used in this study used Sondir data for the Labor Intensive Bridge Project, based on the results of the analysis of the decline in galam and geotextile materials. Then it is known the difference in the value of the decline based on the results of the safety factor value of 3.71 and for geotextiles 1.21. From the value of the safety factor obtained, the reinforcement of galam pile is better than using geotextile.